Penyuluhan Stunting pada Ibu-Ibu PKK di Desa Kendalpayak Kecamatan Pakisaji Kabupaten Malang Jawa Timur - Afifa Irma; Ahisa Novianti (STIKes Ibnu Sina Ajibarang, 2023)
. Stunting is a condition of height according to body length below -2 SD. The short and long term impacts of stunting can affect the cognitive or affective abilities of toddler growth and development. Lack of knowledge on caring for mothers of toddlers related to fulfilling balanced nutrition, especially during the First 1000 Days of Life can have an impact on the occurrence of stunting. This community service is aimed at increasing mothers' knowledge regarding stunting incidents and optimizing 1000 HPK. Implementation of activities in the form of counseling and two-way interactive dialogue. The results of the implementation of community service showed an increase in the knowledge of the counseling participants after being given stunting counseling. Counseling participants looked enthusiastic and actively participated in the activity until the event ended. It is hoped that regular and scheduled counseling programs can further improve welfare and optimize the growth and development of toddlers.